Alkyne-Cobalt-Clusters: Syntheses, Structures and Rearrangements of Metal-Stabilized Propargyl Cations and Radicals - Kaldis, John H. (My University, 2003)
Cobalt-clusters are versatile reagents in organometallic chemistry. Their ability to protect an alkyne allows one to selectively manipulate a ligand without undergoing a competitive reaction from the alkyne. Cobalt-clusters geometrically modify linear alkynes to 136-145° degrees, thereby allowing for some non-traditional alkynyl chemistry to occur. In particular, the focus of this dissertation lies upon the chemistry of cobalt-complexed propargyl alkynols, the ability of cobalt to stabilize neighbouring cations generated from these alcohols, and the chemistry that can be accomplished by altering the steric and electronic effects. We have chosen to study the possibility of inducing migration of various substituents from one terminus of the cobalt-complexed alkyne to the alcoholic site of the propargyl group via protonation of the desired complex. While examining various silanes, and altering the propargyl alcohol itself, we have considered both steric and electronic effects, thereby determining the idealized conditions for such transfers to occur. Furthermore, in our attempts to successfully apply these migrations to several systems, we have acquired a diverse synthetic knowledge of propargyl cobalt-clusters and their intricate reactivity.
An examination of the potential for allyl migrations in norbornyl derivatives revealed several fascinating transformations. Upon protonation with HBF4, [(2-endo-allyldimethylsilyl)ethynylborneol]Co2(CO)6, 63, suffers elimination of water or propene, to yield [(2-allyldimethylsilyl)ethynylborn-2-ene]Co2(CO)6, 68, [(2-endo-dimethylfluorosilyl)ethynylborneol]Co2(CO)6, 69, respectively, and, surprisingly, the tricobalt complex (2-norbornylidene)CHCCo3(CO)9, 70, In contrast, protonation of the terminal alkyne (2-endo-ethynylborneol)Co2(CO)6, 76, an anticipated precursor to 70, led instead to (2-ethynyl-2-bornene)Co2(CO)6, 78, and the ring-opened species (2-ethynyl-4-isopropyl-1-methylcyclohexa-1,3-diene)Co2(CO)6, 79. However, conversion of 76 to 70 was achievable upon prolonged heating at reflux in acetone, thereby also affording the corresponding alcohol, [2-(2-hydroxybornyl)]CH2CCo3(CO)9, 77. A mechanistic rationale is offered for the formation of RCH2CCo3(CO)9 clusters upon protonation of alkyne complexes of the type (RC≡CH)Co2(CO)6.
Our interest in acid-promoted rearrangements in cobalt-clusters led us to novel propargyl radical chemistry induced by using particular solvents. The protonation of (1,1-diphenyl-2-propyn-1-ol)Co2(CO)6, 108, with HBF4 in dichloromethane generates the expected metal-stabilized propargyl cation, and also rearranges to give the tricobalt cluster Ph2C=CH-CCo3(CO)9, 33. In contrast, use of THF as solvent affords the radical (Co2(CO)6)[HC≡C-CPh2·], which dimerizes at the methyne position; subsequent cyclization and carbonylation yields 2,5-bis-(diphenylmethylene)cyclopent-3-en-1-one, 112.
Furthermore, use of a fluorenyl substituent, instead of the diphenyl analogue, has uncovered a route to transition-metal peroxides of general synthetic potential. Treatment of benzyl- or vinyl-dimethylsilylethynylfluoren-9-ol[Co2(CO)6], 53 and 54, respectively, with HBF4 in diethyl ether or THF has afforded the very first known bimetallic transition metal peroxides, 124 and 125.
Finally, the ability of cobalt-clusters to alter the geometry of cycloalkanes has been investigated. Treatment of 1-[axial]-(trimethylsilylethynyl)cyclohexan-1-ol, 129, with dicobalt octacarbonyl results in a conformational ring flip such that the bulky dicobalt-alkyne cluster moiety now occupies the favored equatorial site. However, when a 4-tert-butyl substituent is present, the coordinated alkynyl group retains its original axial or equatorial position.
Complexation of trans-[diaxial]-1,4-bis(triphenylsilylethynyl)cyclohexan-1,4-diol, 142, brings about a chair-to-chair conformational inversion such that both cluster fragments now occupy equatorial sites. In contrast, cis-1,4 bis(triphenylsilylethynyl)cyclohexan-1,4-diol, 143, reacts with Co2(CO)8 to yield the twist-boat conformer, 145, in which the two axial hydroxy substituents exhibit intra-molecular hydrogen bonding. Likewise, the corresponding reaction of cis-1 ,4bis(trimethylsilylethynyl)cyclohexan-1,4-diol, 147, with Co2(CO)8 leads to a twist-boat, 149, but, in this case, the molecules are linked through intermolecular hydrogen bonds. The importance of X-ray crystallography in the unambiguous determination of molecular conformations has been emphasized.
Keywords: alkyne, cobalt, clusters, syntheses, structures, rearrangements, metal-stabilized, cations, radicals, propargyl, reagents, linear, reaction, molecular